Modes de résolution des tensions identitaires en formation : le cas des reconversions vers le métier d’enseignant - Muriel Deltand (Recherches en Éducation)
Based on biographical interviews with professionals involved in training schemes preparing them for a reconversion to the teaching profession, the article analyses the identity strategies and the moments of self-deliberation with oneself that they put in place to deal with the identity tensions that learning the new profession generates in them. Particular emphasis is placed on the identity functions of these strategies as one of the components of the four modes of resolving tensions presented in our results: modes of preservation, rearrangement, reshaping and transformation of identity.